PERBEDAAN PENGARUH MOTIVASI KERJA TERHADAP KINERJA GURU PADA SAAT PANDEMI COVID-19 DAN SEBELUM PANDEMI COVID-19 (STUDI PADA GURU KELAS SDN SE KECAMATAN BINUANG) - Riesca Mohhar (JURNAL KINDAI, 2022)
This study aims to determine and analyze (1) the effect of work motivation on the performance of classroom teachers during the Covid-19 pandemic, (2) the effect of work motivation on the performance of classroom teachers before the Covid-19 pandemic, and (3) differences in the work motivation of classroom teachers during the COVID-19 pandemic. during the Covid-19 pandemic and before the Covid-19 pandemic. This research is a quantitative research with a survey design (non-experimental). The population and sample of this study were 104 PNS class teachers in 22 public elementary schools throughout the Binuang District, divided into 2 clusters with 52 respondents each. Analysis of the data used in this study using simple linear regression analysis and different tests (independent sample t test). The results of the study illustrate the positive influence of work motivation variables on the performance of classroom teachers during the Covid-19 Pandemic and before the Covid 19 pandemic. There are differences in the work motivation variables of classroom teachers during the Covid-19 Pandemic and before the Covid-19 Pandemic, elementary school teachers in Binuang District.